2022
DOI: 10.1002/we.2799
|View full text |Cite
|
Sign up to set email alerts
|

Wind plant power maximization via extremum seeking yaw control: A wind tunnel experiment

Abstract: This work describes the results from wind tunnel experiments performed to maximize wind plant total power output using wake steering via closed loop yaw angle control.The experimental wind plant consists of nine turbines arranged in two different layouts; both are two dimensional arrays and differ in the positioning of the individual turbines. Two algorithms are implemented to maximize wind plant power: Log-of-Power Extremum Seeking Control (LP-ESC) and Log-of-Power Proportional Integral Extremum Seeking Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Several strategies have been proposed to reduce wake interaction and maximize power production 1,2 ; a review is presented in Kheirabadi and Nagamune 3 and Andersson et al 4 Among them, wake steering by yaw control, that is, the intentional application of yaw misalignment to upstream turbines, has been shown to be a promising technique to increase the power production of arrays of aligned turbines 5 and of wind farms. [6][7][8][9][10][11] The power production of the yawed turbines decreases, but their wakes are steered away from the downstream turbines, which increase their power production. As a result, depending on the atmospheric conditions and the turbine spacing, the cumulative power production of the turbine array increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies have been proposed to reduce wake interaction and maximize power production 1,2 ; a review is presented in Kheirabadi and Nagamune 3 and Andersson et al 4 Among them, wake steering by yaw control, that is, the intentional application of yaw misalignment to upstream turbines, has been shown to be a promising technique to increase the power production of arrays of aligned turbines 5 and of wind farms. [6][7][8][9][10][11] The power production of the yawed turbines decreases, but their wakes are steered away from the downstream turbines, which increase their power production. As a result, depending on the atmospheric conditions and the turbine spacing, the cumulative power production of the turbine array increases.…”
Section: Introductionmentioning
confidence: 99%
“…In order to maximize the power production of a wind farm, the wake interaction among the wind turbines must be minimized. Several strategies have been proposed to reduce wake interaction and maximize power production 1,2 ; a review is presented in Kheirabadi and Nagamune 3 and Andersson et al 4 Among them, wake steering by yaw control, that is, the intentional application of yaw misalignment to upstream turbines, has been shown to be a promising technique to increase the power production of arrays of aligned turbines 5 and of wind farms 6–11 . The power production of the yawed turbines decreases, but their wakes are steered away from the downstream turbines, which increase their power production.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we perform multi-row wind farm power optimization through a feedback real-time yaw optimization strategy dubbed the Log-of-power proportional-integral extremum seeking control (LP-PIESC). In [10], the authors conducted wind tunnel experiments with extremum seeking control assuming that only a single row of turbines (the most upstream row) can change its yaw angle to perform wake steering. In the current work, we extend the IOP Publishing doi:10.1088/1742-6596/2767/3/032043 2 approach in [10] to the case when turbines in inner rows within the wind farm can also perform wake steering by yaw control.…”
Section: Introductionmentioning
confidence: 99%
“…In [10], the authors conducted wind tunnel experiments with extremum seeking control assuming that only a single row of turbines (the most upstream row) can change its yaw angle to perform wake steering. In the current work, we extend the IOP Publishing doi:10.1088/1742-6596/2767/3/032043 2 approach in [10] to the case when turbines in inner rows within the wind farm can also perform wake steering by yaw control.…”
Section: Introductionmentioning
confidence: 99%
“…The latter attempts to synthesise control signals directly from measurements of the wind farm. In wind tunnel experiments, a closed-loop, model-free yaw controller (Campagnolo et al, 2016) and extremum-seeking control (Kumar et al, 2023) have been demonstrated to produce power gains from wake steering under steady flow conditions. Extremum-seeking control has also been demonstrated in large-eddy simulation (LES) (Ciri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%